Assessment of immunization status in the slums of Surat by 15 clusters multi indicators cluster survey technique - Sharma Rashmi; Desai Vikas; Kavishvar Abhay (Wolters Kluwer Medknow Publications, 2009)
Research Question: What is the immunization status of children in the slums of Surat and what changes has it undergone in recent times? Objective: To assess the immunization status of children between the ages of 12 and 23 months in the slums of Surat and to compare it with the MICS from previous years. Study Design: This was a community-based cross-sectional study conducted in 15 clusters. Settings: 15 urban slums selected out of a total of 299 slums using the cluster sampling method. Study Tool: The Multi Indicator Cluster Sampling (MICS) method was used for sample selection and the proforma designed by UNICEF was used as a study tool. Statistical Analysis: Simple proportions and a Chi-square test. Results: Only 25% of the children between the ages of 12 and 23 months were fully immunized; coverage was highest for BCG (75%) and lowest for measles (29.9%). As far as the dropout rate is concerned, it was 60.2%, 31.9%, and 31.5% for BCG to measles, DPT 1 to DPT 3 , and OPV 1 to OPV 3 , respectively. Vitamin A was taken by only 28.9% of the subjects. Between the two, female children were more disadvantaged in terms of vaccination. When compared with the coverage of 1997 and 1998, the current coverage is poor, more so in relation to DPT and OPV.